Stabilising control strategy for cyber-physical power systems - Ekomwenrenren, Etinosa; Alharbi, Hatem; Elgorashi, Taisir; Elmirghani, Jaafar; Aristidou, Petros (My University, 2019)
The cyber-physical nature of electric power systems has increased immensely over the past decades, with advanced communication infrastructure paving the way. It is now possible to design wide-area controllers, relying on remote monitor and control of devices that can tackle power system stability problems more effectively than local controllers. However, their performance and security relies extensively on the communication infrastructure and can make power systems vulnerable to disturbances emerging on the cyber side of the system. In this study, the authors investigate the effect of communication delays on the performance of wide-area damping controllers designed to stabilise oscillatory modes in a cyber-physical power system (CPPS). They propose a rule-based control strategy that combines wide-area and traditional local stabilising controllers to increase the performance and maintain the stable operation of CPPS. The proposed strategy is validated on a reduced CPPS equivalent model of Great Britain.
Keywords: Controllers; Cyber Physical System; System stability; Communication delays; Communication infrastructure; Control strategies